Temporal evolution of collar lesions associated with ash dieback and the occurrence of Armillaria in Belgian forests. Issue 4 (29th January 2016) - Chandelier, A.; Gerarts, F.; San Martin, G.; Herman, M.; Delahaye, L.
Summary: Ash dieback, caused by the fungus Hymenoscyphus fraxineus, has been observed in Europe for several years. In Belgium, the disease was first reported in 2010. Besides crown defoliation and dieback, collar lesions have sometimes been reported. To evaluate the prevalence and the progression of collar lesions and crown defoliation in ash dieback‐affected stands of various ages, a survey was conducted in 2013 and 2014 on 268 ash trees ( Fraxinus excelsior ) originating from 17 Walloon forest stands. The results showed that the proportion of trees with collar lesions greatly increased between June 2013 and September 2014 and that there appeared to be no significant link between a tree's diameter‐at‐breast height (DBH) and collar lesion occurrence. The mean percentage of defoliation increased in each forest stand across time, with observations conducted in September 2013 and 2014 showing a positive correlation with the mean percentage of trees with collar lesions. Molecular tests were carried out on 103 additional trees originating from 12 of the 17 stands to evaluate the occurrence of H. fraxineus and Armillaria spp. at the collar level. Most of the trees (98%) were infected by H. fraxineus . In contrast, only 41% of the samples were infected with Armillaria spp., most commonly A. gallica and A. cepistipes . This study discusses the role of Armillaria spp. and the rapid increase in the number of trees with collar lesions within the context of the evolution of ash dieback in Europe.